Cloud-Enabled Social Network Mining for Advanced Recommendation Systems: An Integrated Data Mining and Social Network Analysis Approach - Jaishree Jain, Santosh Kumar Upadhyay, Sharvan Kumar, Neerja Arora (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Recommendation systems play a crucial role in assisting users in discovering relevant and personalized content in social networks. For recommendation system data mining has a profound impact on several domains, including databases, artificial intelligence, machine learning, and social networks. It plays a crucial role in driving significant research advancements in the field. In today's fast-paced world, where data is rapidly expanding and information retrieval poses complex challenges, users increasingly demand valuable insights from their vast datasets. Social networks have emerged as a fascinating domain that has made substantial contributions to data mining research, ushering in a new era of possibilities. To determine the intrusion index based on the source address of the network security alarm, a simulation test is run. The findings demonstrate that this strategy can successfully implement cloud network security situation awareness as the related window attack index drops as soon as the security event is cancelled. You can accurately detect changes in network security circumstances using the suggested technique